Additive manufacturing of cellular structures: Multiscale simulation and optimization - Mergheim, Julia; Breuning, Christoph; Burkhardt, Christian; Hübner, Daniel; Köpf, Johannes; Herrnböck, Ludwig; Yang, Zerong; Körner, Carolin; Markl, Matthias; Steinmann, Paul; Stingl, Michael (Journal of Manufacturing Processes, 2023)
This paper introduces a multiscale and multi-purpose simulation framework to investigate selective beam melting processes for metallic cellular structures along the complete process chain, up to the topology optimization of components made of cellular materials. Process simulation methods on various length scales are introduced to analyze the relation of process strategies and resulting properties of the cellular materials, as e. g. warpage, residual stresses, material grain structure and surface roughness. Numerical homogenization methods are applied to investigate the influence of the grain structure and the topology of the cellular materials on their mechanical properties. Based on these process-dependent mechanical properties, a two-scale optimization of components made of cellular material is performed, aiming in particular on optimizing the buckling resistance of the structures. The interfaces between the different simulation tools are specified and illustrate the flexibility of the numerical framework. It is shown that consistent simulations of additive manufacturing of cellular materials - from the manufacturing process to the optimized component - provide important insights into process-structure interactions and enable tailored additive manufacturing processes.
CRIS-Team WoS Importer:2023-06-02

Comprehensive numerical investigation of laser powder bed fusion process conditions for bulk metallic glasses - Yang, Zerong; Markl, Matthias; Körner, Carolin (Additive Manufacturing, 2024)
The successful application of laser powder bed fusion (PBF-LB/M) for fabricating bulk metallic glass (BMG) parts heavily relies on the development of effective process strategies. An optimal process strategy for BMGs is required to go beyond manufacturing defect-free parts and address the critical aspect of minimizing crystallization. However, traditional trial-and-error experimental methods for process development are time-consuming and costly. This paper uses an in-house developed simulation software, SAMPLE2D, to systematically explore PBF-LB/M process conditions for BMGs, with the Zr-based glass-forming alloy Zr59.3Cu28.8Al10.4Nb1.5 (at.%, trade name: AMZ4, AMLOY-ZR01) as an example. We uncover that BMG crystallization during PBF-LB/M is a localized phenomenon, primarily induced by short-range in-situ heat treatment. We comprehensively explore process conditions, encompassing laser beam-related parameters (beam power, speed, diameter, and line offset), as well as powder bed-related parameters (powder layer thickness, preheating temperature, and oxygen level of AMZ4). Leveraging insights derived from the parameter study, we delve into innovative scanning strategies. Various scanning strategies are explored, including line jumping, adding waiting times, translating the scan pattern, and rotating the scan pattern. Remarkably, our findings highlight line jumping as a highly effective scanning strategy to reduce crystallization while maintaining relative density. While either layer-wise translation or non-180° rotation of the scan pattern is generally not recommended, when focusing solely on consolidation and crystallization aspects. This study not only provides an in-depth understanding of how PBF-LB/M process conditions shape the properties of BMG parts, but also offers a fresh perspective on applying PBF-LB/M technology in BMG part productio
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion (PBF-LB/M); Process condition; Numerical simulation

Effect of scanning strategies on grain structure and texture of additively manufactured lattice struts: A numerical exploration - Yang, Zerong; Koepf, Johannes A.; Markl, Matthias; Körner, Carolin (Advanced Engineering Materials, 2024)
Electron beam powder bed fusion (PBF-EB) is a promising technology for fabricating complex parts with near-net-shape precision. Moreover, PBF-EB offers a unique opportunity to tailor the microstructure, thereby tuning local mechanical properties. Numerical simulation has emerged as a powerful tool for predicting the evolution of texture and grain structure during PBF-EB. Herein, the in-house developed and experimentally validated simulation software, SAMPLE3D, is employed to investigate the impact of scanning strategy on the texture and grain structure of CMSX-4 in PBF-EB-processed thin tilted lattice struts, commonly found in cellular structures. The core of SAMPLE3D consists of a finite difference solver for temperature field computation and a cellular automaton model for simulating grain structure evolution. Nine distinct scanning strategies are systematically explored. The resulting texture and grain structures are meticulously compared and comprehensively discussed. Notably, the contour scanning strategy yields distinctive texture and grain structures compared to other explored scanning strategies. This study highlights the capability of SAMPLE3D in assisting microstructure customization in the PBF-EB process, and advances the understanding of the relationship between PBF-EB scanning strategy and resulting microstructure in tilted lattice struts.
CRIS-Team Scopus Importer:2024-08-09
Keywords: additive manufacturing; grain structures; microstructures; numerical simulation; powder bed fusion; superalloys; texture

Evolution of an industrial-grade Zr-based bulk metallic glass during multiple laser beam melting - Yang, Zerong; Wang, Hongcai; Krauß, Sebastian; Huber, Florian; Merle, Benoit; Schmidt, Michael; Markl, Matthias; Körner, Carolin (Journal of Non-Crystalline Solids, 2022)
Selective laser melting (SLM), taking advantage of its inherent rapid cooling rates and near-net-shape forming ability, has been employed to fabricate bulk metallic glasses (BMGs). However, crystallization is frequently triggered during the SLM process, which results in the loss of advantageous properties of BMGs, such as extremely high hardness and near-theoretical yield strength. Although many studies have been conducted to investigate SLM of BMGs, there is still a lack of knowledge about the microstructural and compositional evolution during the laser beam processing, particularly the micromechanical property response upon crystallization. In the present work, a systematic investigation is performed to gain a much better understanding about the evolution of microstructure and composition as well as the corresponding micromechanical property change during multiple laser beam melting. The material used in this study is an industrial-grade Zr-based BMG Zr59.3Cu28.8Al10.4Nb1.5 (AMZ4) with two different oxygen levels. AMZ4 demonstrates its good thermal stability by the fact that observable crystalline structure appears around the melt pool only after more than once laser beam treatment. The compositional stability of AMZ4 is manifested by the homogeneous elemental distribution on the melt pool area after even twenty-five laser beam remelting. The laser-metal interaction, melting and subsequent solidification are not effectively influenced by the emerging and expanding of crystallization zone (or heat affected zone, HAZ). Higher oxygen content results in not only a larger HAZ but also more quenched-in nuclei at the melt pool bottom. The HAZ does not exhibit a fully crystallized structure, but rather has a mixture of amorphous and crystalline phases. Crystallization of AMZ4 leads to an increase in hardness and Young’s modulus of the materia
Keywords: Bulk metallic glass; Crystallization; Laser beam melting; Selective laser melting; Additive manufacturing

Isothermal crystallization kinetics of an industrial-grade Zr-based bulk metallic glass - Yang, Zerong; Al-Mukadam, Raschid; Stolpe, Moritz; Markl, Matthias; Deubener, Joachim; Körner, Carolin (Journal of Non-Crystalline Solids, 2021)
Bulk metallic glasses (BMGs), due to their amorphous structure, exhibit remarkable mechanical properties, and there is an increasing interest in their commercialization. For the industrial fabrication of BMG, knowledge about the isothermal crystallization kinetics of industrial-grade BMG is required. Previous investigations on isothermal crystallization kinetics are mainly based on high-purity samples with very good glass forming ability and/or mainly limited to the low temperature regime. In the present study, a systematic investigation on the isothermal crystallization kinetics of an industrial-grade Zr-based BMG (Zr59.3Cu28.8Al10.4Nb1.5 at.%, trade name: AMZ4) has been performed using conventional and flash differential scanning calorimetry. We report the time-temperature-transformation (TTT) diagrams of the AMZ4 with two different oxygen levels. The diagrams cover the temperature range from glass transition temperature up to liquidus temperature, that have the typical “C-shaped” noses. Faster crystallization of the higher oxygen level AMZ4 was observed, and the underlying mechanisms were investigated. The universal isothermal Johnson-Mehl-Avrami-Kolmogorov (JMAK) model was employed to model the isothermal crystallization kinetics. Satisfactory match was achieved between the experimental facts and the JMAK model, and the interfacial energies between the crystalline phase and liquid were determined as 0.04 J/m2 for the industrial-grade AMZ4. The crystallization fraction dependence of Avrami index and activation energy is studied and found to be neglectable in the JMAK modeling. The critical casting thicknesses were estimated based on the TTT diagrams.
Keywords: Crystallization kinetics; Bulk metallic glass; JMAK Model; Classical nucleation theory; Time-temperature-transformation diagram; Fast scanning calorimetry; Selective laser melting

Modeling and Simulation of Bulk Metallic Glass Crystallization During Laser Powder Bed Fusion - Yang, Zerong (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)
Bulk metallic glasses (BMGs) exhibit many exceptional mechanical properties, making them promising structural materials in diverse industries. These properties derive from their characteristic amorphous structure. However, conventional processing technologies, due to limited cooling rates, face challenges in preventing crystallization to maintain amorphous structures. This limitation restricts the fabrication of complex BMG structures with substantial section thickness. Consequently, it remains challenging to realize the full spectrum of attractive properties offered by BMGs through conventional processing technologies. In contrast, laser powder bed fusion (PBF-LB/M), with its rapid cooling rates at the solidification front, shows great promise for manufacturing BMG parts. Yet, to achieve success, it is crucial to develop optimal process strategies that can effectively minimize both crystallization and process defects. Unfortunately, the current lack of understanding regarding BMG crystallization during PBF-LB/M forces us to heavily depend on trial-and-error experiments for process development. This approach, however, is often not only time-consuming but also costly. This thesis aims to attain a profound and comprehensive understanding of the crystallization behavior of BMGs during PBF-LB/M and develop a numerical tool that can significantly assist in the PBF-LB/M process development. The numerical work builds upon our in-house simulation software, SAMPLE2D, originally developed for simulating the electron beam powder bed fusion process. Consequently, this thesis focuses on two key modeling aspects: laser beam absorption and crystallization. Laser beam absorption was modeled using a ray-tracing approach, considering reflection, refraction, and absorption. The emphasis was on calculating the laser beam absorption coefficient, accounting for its dependence on the angle of incidence and temperature, based on fundamental physical laws. Model validation involved comparing simulation-predicted melt pool geometries with experimentally observed ones, revealing a satisfactory agreement between the two. Modeling of the crystallization behavior serves as the core focus of this thesis. Experimentation provided insights into primary physical effects to consider in the modeling efforts. The modeling approach revolved around the utilization of a phenomenological phase transformation model, specifically the Nakamura model. For numerical implementation, a two-step Euler method was devised. Model parameters were determined through isothermal crystallization experiments, providing essential inputs for the simulation. Experimental validation was achieved by comparing single-track-multi-pass and multi-layer PBF-LB/M results with simulation outcomes. Throughout the study, the glass-forming alloy Zr59.3Cu28.8Al10.4Nb1.5 (at.%) was used as a representative example. The robust agreement between experimental and simulation results allowed for the extensive application of the extended SAMPLE2D, enabling a comprehensive investigation of PBF-LB/M process conditions, encompassing beam- and powder bed-related parameters, as well as scanning strategies. Numerical insights unveiled that BMG crystallization during PBF-LB/M is a localized phenomenon primarily induced by short-range in-situ heat treatment. Furthermore, a general process development guideline was proposed: First, utilize an appropriate energy input to minimize porosity; Second, within the parameter space capable of fabricating dense parts, minimize the energy input and select parameters that yield a more even energy distribution; Third, optimize the scanning strategy to further reduce crystallization. Notably, the line jumping scanning strategy was highlighted as an effective means of minimizing crystallization while maintaining relative density. Therefore, this thesis not only deepens our comprehension of BMG crystallization during PBF-LB/M but also furnishes the industry with a readily applicable numerical tool to aid in practical PBF-LB/M process developmen
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion (PBF-LB/M); Simulation; Modeling; Additive manufacturing

Modeling laser beam absorption of metal alloys at high temperatures for selective laser melting - Yang, Zerong; Bauereiß, Andreas; Markl, Matthias; Körner, Carolin (Advanced Engineering Materials, 2021)
Selective Laser Melting (SLM) or laser beam powder bed fusion of metals (PBF-LB/M) is a promising technology to fabricate metallic components with complex geometries. However, determining process windows for specific materials and SLM machines by trial‐and‐error experiments is time consuming and expensive. Numerical simulation has been demonstrated as an efficient way to aid the process development. A crucial aspect in simulating SLM is the absorption and reflection of the laser heat source by the material. While there exist elaborated ray tracing approaches and absorption models, the most important drawback is to measure a reliable reflection coefficient of the material for different temperatures and phases. In this work, we discuss the application of a laser beam absorption model for SLM of metal alloys in the high temperature regime. The model bases on fundamental physical laws by taking reflection, refraction and absorption into account. The corresponding reflection coefficient is related to other physical quantities, like the electrical resistivity, which are easier to measure. The computed reflection coefficients by this model are compared with reflection coefficient measurements of liquid NiFe alloys and with SLM of SS316L and Ti-6Al-4V. Finally, the laser beam absorption model is implemented in SAMPLE2D a software for simulation of additive manufacturing on the powder scale, and is exemplary applied on single track melting experiments on compact Ti-6Al-4V plates.<br

Predictive simulation of bulk metallic glass crystallization during laser powder bed fusion - Yang, Zerong; Markl, Matthias; Körner, Carolin (Additive Manufacturing, 2022)
Laser powder bed fusion (L-PBF) has been employed to fabricate bulk metallic glass (BMG) parts. However, traditional experimental trial-and-error methods to determine process parameters for specific materials and L-PBF machines are time-consuming and expensive. In this paper, a phenomenological crystallization model, namely the Nakamura model, is coupled with L-PBF process simulation. A convenient approach for the crystallization parameter determination and a two-step Euler method for the numerical implementation has been developed. Numerical simulations are performed using the material parameters of a Zr-based BMG Zr59.3Cu28.8Al10.4Nb1.5 (at.%, trade name: AMZ4). The numerical results are validated by comparing with experimental results from different perspectives. Based on the numerical findings, a comprehensive understanding of BMG crystallization behavior during L-PBF is gained. In the end, the crystallization model is implemented in our in-house developed software SAMPLE2D. SAMPLE2D simulation results are presented, whereby the L-PBF process window for fully amorphous AMZ4 parts is explored. Thereby, it is believed that the developed numerical software can be applied to aid process development for BMGs by taking the crystallization phenomenon into account.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Bulk metallic glass; Crystallization; Laser powder bed fusion; Nakamura model

Revealing bulk metallic glass crystallization kinetics during laser powder bed fusion by a combination of experimental and numerical methods - Yang, Zerong; Huber, Florian; Krapf, Anna; Merle, Benoit; Markl, Matthias; Schmidt, Michael; Körner, Carolin (Journal of Non-Crystalline Solids, 2023)
Laser powder bed fusion (PBF-LB/M) has been used to fabricate bulk metallic glass (BMG) parts. However, there is still a lack of understanding about the crystallization behavior of BMGs during PBF-LB/M. This article aims to combine experimental and numerical methods to gain a more comprehensive understanding of the BMG crystallization kinetics during PBF-LB/M. The material used in this work is an industrial-grade BMG commercially known as AMZ4 (Zr59.3Cu28.8Al10.4Nb1.5, at.%). The samples prepared by PBF-LB/M were characterized by optical microscopy, scanning electron microscopy, and nanoindentation. Simulations were performed using our in-house developed software with setups mimicking the PBF-LB/M experiment. The experimental and numerical results are compared and discussed in detail. The most important finding is that BMG crystallization in PBF-LB/M is a very localized phenomenon, mainly caused by short-range in situ heat treatment. Here, short-range in-situ heat treatment refers to concomitant heat treatment that occurs during the processing of the current melt line, very few subsequent melt lines, and very few subsequent layers. This work provides insight into the BMG crystallization phenomenon that occurs during PBF-LB/M processing, especially its underlying crystallization kinetics. Furthermore, this work demonstrates the usefulness of our in-house developed simulation software in guiding PBF-LB/M process development for BMGs and BMG composites.<br
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion; Additive manufacturing; Numerical simulation

SAMPLE3D: A versatile numerical tool for investigating texture and grain structure of materials processed by PBF processes - Yang, Zerong; Kuesters, Yves; Logvinov, Ruslan; Markl, Matthias; Körner, Carolin (IVth International Conference on Simulation for Additive Manufacturing (Sim-AM 2023), 2023)
Powder Bed Fusion (PBF) not only enables the fabrication of metal parts with complex geometries in near-net-shape, but also offers the potential to tailor the microstructure and, consequently, the mechanical properties of the final product. In this contribution, we present our in-house developed simulation software SAMPLE3D (Simulation of Additive Manufacturing on the Powder scale using a Laser or Electron beam in 3D), which is designed specifically for simulating grain structure evolution during PBF processes. The core of SAMPLE3D is composed of a finite difference model and a cellular automaton model. The finite difference model is used to obtain the temperature field caused by an electron or laser beam. This temperature field is further used in the cellular automaton model to simulate grain structure development where grain selection as well as nucleation is considered. A range of information can be extracted from the simulation results, such as texture, grain morphology, and grain boundary arrangement. SAMPLE3D provides a way to get insight into the relationship between PBF process strategies and microstructures. SAMPLE3D has been employed to investigate the texture and grain structure evolution of various materials in different research projects.<br
Keywords: Material microstructure; Cellular automata; Grain growth; Powder bed fusion; Texture